PREBIOTIC POTENTIAL OF ENZYME SUPPLEMENTED WHEAT OFFAL IN BROILER CHICKENS. - Abosede, Aderibigbe Temitayo; Omolola, Opowoye Ibiyemi; Olutimehin, Atteh Job; Okukpe, Kehinde Matthias (Journal of Agricultural Sciences (Belgrade), 2017)
Recent development of antibiotics-resistance pathogens in poultry which poses threat to human health has necessitated the search for alternative to antibiotic growth promoters (AGPs) to improve gut microflora in poultry diets. One of the alternatives to AGPs is probiotics which are beneficial organisms. Prebiotics, are by-products of digestion of polysaccharides which poultry do not have enzymes to digest are food for probiotics. Advent of enzymes makes this digestion possible. The prebiotic potentials of enzyme supplemented high fibre feedstuffs (HFFs) are not known. This study was conducted to assess the prebiotics potential of xylanase enzyme supplemented wheat offal on broiler chickens (in-vivo). The replacement of maize with wheat offal irrespective of levels supplemented with 100ppm xylanase enzyme caused a reduction in feed intake and an increase in weight gain and better FCR. Birds fed diet with 20% wheat offal supplemented with xylanase enzyme out-performed birds fed diets with 10 or 30% wheat offal supplemented with xylanase enzyme and birds fed the control diet. The weights of vital organs were in good health conditions. Identification of microbes (Fungi and Bacteria) showed that dietary levels of wheat offal (10, 20 or 30% inclusion) with supplementation of enzyme xylanase enhanced the growth of beneficial microbes which resulted in inhibition or elimination of the opportunistic/pathogenic microbes. It was concluded that enzyme supplementation of high fibre feedstuffs could improve growth performance, nutrient retention and increased concentration of beneficial microbes in gut. Use of enzymes is therefore recommended when HFFs are required as prebiotic source in the gut of broilers.